Changing Thoroughly? A Playwright / Researcher Reflection on Research-based Theatre and 'Being Frank' - Summers, Chris (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
This paper explores the educational possibilities and limitations of Deakin University’s CHASE (Centre for Health through Action on Social Exclusion) trans and gender diverse Research-based Theatre project, Being Frank, in Victoria, Australia, 2016-2020. Adopting the perspective of the playwright / researcher, this paper documents the tensions between playwriting as artistic practice and Research-based Theatre within scholarly and educational contexts. The paper critically outlines the advisory group sessions, workshops, and presentations of the project - including within secondary school, tertiary and community-based programs - raising questions related to ethics / representation when seeking to dramatise complex issues. This paper offers Research-based Theatre practitioners, educational workers and artist / researchers insights into using theatre to advocate for inclusion and diverse perspectives.